2000
DOI: 10.1002/(sici)1098-2795(200001)55:1<8::aid-mrd2>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Glowing zebrafish: Integration, transmission, and expression of a single luciferase transgene promoted by noncovalent DNA–nuclear transport peptide complexes

Abstract: The development of vehicles driving foreign DNA into the cell nucleus is essential for effective cellular gene transfer applications. We report that noncovalent binding of nuclear localization signal (NLS) peptides to plasmid DNA enhances nuclear uptake of the DNA and promotes germline integration, inheritance, and expression of a single copy of a luciferase reporter gene in zebrafish. As few as 10 DNA-NLS complexes (0.06 fg plasmid DNA) cytoplasmically injected are sufficient to produce germline-transgenic ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
11
1
2
Order By: Relevance
“…This differs from the results of other studies, in which transgenes often had multiple integration patterns in F1 progeny derived from the same founder (Alam et al, 1996;Culp et al, 1991;Liang et al, 2000;Penman et al, 1991). This clonal integration pattern makes it much easier to establish stable homozygotes.…”
Section: Integration Pattern Of Transgenes Flanked By Aav-itrscontrasting
confidence: 92%
See 2 more Smart Citations
“…This differs from the results of other studies, in which transgenes often had multiple integration patterns in F1 progeny derived from the same founder (Alam et al, 1996;Culp et al, 1991;Liang et al, 2000;Penman et al, 1991). This clonal integration pattern makes it much easier to establish stable homozygotes.…”
Section: Integration Pattern Of Transgenes Flanked By Aav-itrscontrasting
confidence: 92%
“…Cytoplasmic microinjection of transgenes results in highly mosaic founder gonads and low germ-line transmission rates. Thus, many progeny must be screened by dot blot or PCR to find transgenic founders (Stuart et al, 1988;Culp et al, 1991;Liang et al, 2000). A reporter gene helps reduce the screening effort and makes it possible to monitor the expression pattern of the transgene noninvasively.…”
Section: Stable Transmission Of Transgenes Flanked By Aav-itrsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the NLS peptides may constitute a valuable tool to improve the efficiency of transgenesis in several species. Several reports confirm the potential use of nuclear targeting peptides, which are non-covalently bound to vector DNA, to enhance the efficiency of biotechnological non-viral gene transfer applications (Malecki, 1996;Aronsohn and Hughes, 1998;Schwartz et al, 1999;Liang et al, 2000;Chan and Jans, 2001).…”
Section: Non-covalent Association Of Dna With Nls Sequence-bearing Symentioning
confidence: 97%
“…Second, the transfection efficiency needs to be increased and/or expression of transgenes with increased potency needs to be optimized to completely suppress tumor growth rather than simply decrease the growth rate. Examples of technology that can overcome these limitations are reduction of nonspecific cell interactions with masking technologies, such as incorporating polyethylene glycol; transfection complex targeting with ligands to yield selective uptake to tumor vasculature; coformulation of agents to facilitate endocytic vacuole escape of the delivered gene, such as pH-dependent lytic peptides 21,22 or proton-absorbing polymers; 23 and increased nuclear uptake of the plasmid either by incorporating nuclear localization agents 24 or by simply including DNA sequences that endogenous nuclear localization proteins can recognize. 25 There are several alternative types of genes that can be expressed with increased potency.…”
Section: Discussionmentioning
confidence: 99%